Efficacy of the Diabeloop closed‐loop system to improve glycaemic control in patients with type 1 diabetes exposed to gastronomic dinners or to sustained physical exercise. Issue 3 (16th October 2019) - Hanaire, Hélène; Franc, Sylvia; Borot, Sophie; Penfornis, Alfred; Benhamou, Pierre‐Yves; Schaepelynck, Pauline; Renard, Eric; Guerci, Bruno; Jeandidier, Nathalie; Simon, Chantal; Hannaert, Patrick; Xhaard, Ilham; et al.
Abstract: Aims: To compare closed‐loop (CL) and open‐loop (OL) systems for glycaemic control in patients with type 1 diabetes (T1D) exposed to real‐life challenging situations (gastronomic dinners or sustained physical exercise). Methods: Thirty‐eight adult patients with T1D were included in a three‐armed randomized pilot trial (Diabeloop WP6.2 trial) comparing glucose control using a CL system with use of an OL device during two crossover 72‐hour periods in one of the three following situations: large (gastronomic) dinners; sustained and repeated bouts of physical exercise (with uncontrolled food intake); or control (rest conditions). Outcomes included time in spent in the glucose ranges of 4.4‐7.8 mmol/L and 3.9‐10.0 mmol/L, and time in hypo‐ and hyperglycaemia. Results: Time spent overnight in the tight range of 4.4 to 7.8 mmol/L was longer with CL (mean values: 63.2% vs 40.9% with OL; P ≤ .0001). Time spent during the day in the range of 3.9 to 10.0 mmol/L was also longer with CL (79.4% vs 64.1% with OL; P ≤ .0001). Participants using the CL system spent less time during the day with hyperglycaemic excursions (glucose >10.0 mmol/L) compared to those using an OL system (17.9% vs 31.9%; P ≤ .0001), and the proportions of time spent during the day with hyperglycaemic excursions of those using the CL system in the gastronomic dinner and physical exercise subgroups were of similar magnitude to those in the control subgroup (18.1 ± 6.3%, 17.2 ± 8.1% and 18.4 ± 12.5%, respectively). Finally, times spent in hypoglycaemia were short and not significantly different among the groups. Conclusions: The Diabeloop CL system is superior to OL devices in reducing hyperglycaemic excursions in patients with T1D exposed to gastronomic dinners, or exposed to physical exercise followed by uncontrolled food and carbohydrate intake.